1995
DOI: 10.1111/j.1365-2230.1995.tb02675.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatomyositis treated with high-dose intravenous immunoglobulins and associated with panniculitis

Abstract: Polymyositis and dermatomyositis are idiopathic inflammatory myopathies characterized by subacute symmetrical weakness of proximal limb and trunk muscles. Dermatomyositis is distinguished from polymyositis by the presence of rash. We describe an adult patient with treatment-resistant childhood-type dermatomyositis who made a good response to high dose intravenous immunoglobulins. Additionally, there was evidence of panniculitis which is an unusual histopathological finding in dermatomyositis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 12 publications
0
19
0
3
Order By: Relevance
“…Other drugs such as methotrexate or intravenous immunoglobulin are used less frequently in patients who fail to respond to steroids. 4,10 It is noteworthy that the difference between this condition and lupus panniculitis is that in the former antimalarial drugs have no effect. 3 The presence of panniculitis in a patient with dermatomyositis is believed to be indicative of good prognosis, since almost all the cases respond well to treatment and malignancy has been detected in only one case.…”
Section: Discussionmentioning
confidence: 99%
“…Other drugs such as methotrexate or intravenous immunoglobulin are used less frequently in patients who fail to respond to steroids. 4,10 It is noteworthy that the difference between this condition and lupus panniculitis is that in the former antimalarial drugs have no effect. 3 The presence of panniculitis in a patient with dermatomyositis is believed to be indicative of good prognosis, since almost all the cases respond well to treatment and malignancy has been detected in only one case.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a major pathological feature besides the in£ammatory cell in¢ltration along the basement membrane of the muscle ¢bers is the deposition of complement, the membrane attack complex C5b-C9, in intramuscular capillaries. In a number of clinical trials, IGIV has shown e⁄cacy in returning muscle strength, reducing creatin kinase levels, and reducing the need for corticosteroids (Roifman et al, 1987;Dalakas et al, 1993;Collet et al, 1994;Sabroe et al, 1995;Furuya et al, 1998). Both muscle and cutaneous (ulcer) manifestations respond.…”
Section: Mechanism Of Action Of Igivmentioning
confidence: 95%
“…Panniculitis is an usual finding in dermatomyositis and, although it was first described in 1924, there few case reports describing this entity in the subsequent century 39,40 . Despite the paucity of clinical reports, histopathologic studies suggest that up to 10% of dermatomyositis biopsies show focal panniculitis, suggesting subclinical panniculitis may be an under-recognized feature 41 .…”
Section: Dermatomyositismentioning
confidence: 99%
“…For dermatomyositis, prednisone is typically initiated at 0.5–1.0 mg/kg/day and then tapered slowly based on clinical response. If panniculitis lesions appear in the setting of a prednisone taper, an increase in dose of corticosteroids may be beneficial 39,40,48 . Intravenous methylprednisilone is sometimes used in pulse dosing for the three consecutive days at 1 gram/daily for severe cases and has also been reported efficacious in oral formulation for the treatment of panniculitis in dermatomyositis 45 .…”
Section: Dermatomyositismentioning
confidence: 99%
See 1 more Smart Citation